2010
DOI: 10.1002/cpp.732
|View full text |Cite
|
Sign up to set email alerts
|

Gender identity, research self‐efficacy and research intention in trainee clinical psychologists in the UK

Abstract: This study tested, with a sample of United Kingdom (UK) trainee clinical psychologists, part of an existing model of factors that influence clinical psychologists' levels of research activity, in which gender identity is hypothesized to influence research self-efficacy and this in turn strength of intention to do research. A sample of 121 trainee clinical psychologists (56 men and 65 women) completed a measure of gender identity, research intention, and a research self-efficacy scale. Results indicated no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
2
18
1
Order By: Relevance
“…The significant relationship between past behavior and intention was observed in previous studies (e.g. Côté, Gagnon, Houme, Abdeljelil, & Gagnon, 2012), and the relationship between some gender characteristics and research intention was found in the study by Wright and Holttum (2012).…”
Section: Research Focusessupporting
confidence: 57%
See 3 more Smart Citations
“…The significant relationship between past behavior and intention was observed in previous studies (e.g. Côté, Gagnon, Houme, Abdeljelil, & Gagnon, 2012), and the relationship between some gender characteristics and research intention was found in the study by Wright and Holttum (2012).…”
Section: Research Focusessupporting
confidence: 57%
“…Those few studies included the line of research involved by Sue Holttum -i.e. Holttum and Goble (2006); Wright and Holttum (2012);and Eke, Holttum, and Hayward (2012). These studies looked into the field of psychology and into the developed context of the United Kingdom.…”
Section: Research Intention: Theoretical and Empirical Basesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender identity may also relate to that of researcher (Hicks, 1999). Wright and Holttum (2011) looked at the relationship between gender identity and intention to conduct future research in a sample of trainee clinical psychologists, reporting that masculinity was related to greater intention, mediated by research self-efficacy.…”
Section: Future Researchmentioning
confidence: 99%